2018
DOI: 10.5603/gp.a2018.0087
|View full text |Cite
|
Sign up to set email alerts
|

Ocular perfusion pressure and intraocular pressure in pregnant women with severe preeclampsia

Abstract: Objectives: The aim of this study was to investigate whether severe preeclampsia (SPE) affects intraocular pressure (IOP) and ocular perfusion pressure (OPP). Material and methods: This prospective and comparative study included 64 pregnant females, allocated into 2 groups as Group 1 (31 pregnant women with SPE) and Group 2 (33 normotensive pregnant women). IOP, systolic and diastolic blood pressure, OPP of all the subjects were measured after 20 weeks of gestation and prior to labor and medical therapy. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
3
4
0
1
Order By: Relevance
“… 31 33 34 This study found that intraocular pressure was significantly higher among preeclampsia cases, as reported by previous authors. 18 The ocular parameters in this study were generally similar between the right and left eye, and this similarity has been previously reported. 18 The ocular parameters were similar between women with mild and severe preeclampsia in this study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“… 31 33 34 This study found that intraocular pressure was significantly higher among preeclampsia cases, as reported by previous authors. 18 The ocular parameters in this study were generally similar between the right and left eye, and this similarity has been previously reported. 18 The ocular parameters were similar between women with mild and severe preeclampsia in this study.…”
Section: Discussionsupporting
confidence: 89%
“… 18 The ocular parameters in this study were generally similar between the right and left eye, and this similarity has been previously reported. 18 The ocular parameters were similar between women with mild and severe preeclampsia in this study. This finding has also been reported by previous studies, 18 but other studies have shown significantly higher mean values for resistivity index and pulsatility index among preeclampsia cases.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations